Pengembangan Media Pembelajaran Berbasis Android Menggunakan Powerpoint Dan I-Spring Suite 10 Pada Materi Segitiga Dan Segiempat Kelas VII MTS Negeri Kupang - La Zaiba, Nazla Sahra Ramadhani; Samo, Damianus D.; Nubatonis, Ofienty Elyada (Universitas Nusa Cendana, 2024)
This research aims to develop valid, practical, and effective Android-based mathematics learning media using Powerpoint and Ispring Suite 10 on triangles and quadrilaterals for class VII MTs Negeri Kupang. The method used in this research is the Research and Development method using the ADDIE model. The data collection techniques and instruments used were interviews, questionnaires, and tests. The data analysis techniques used are qualitative and quantitative descriptive analysis techniques. The research results show that Android-based learning media on the triangle and quadrilateral material meets the criteria of being valid, practical, and effective. The results of the feasibility of learning media were obtained from the assessment of 3 material and media experts with an average validity of 4.61 and included in the